Determination of Telmisartan and Hydrochlorothiazide Using HPTLC in Human Plasma: Development and Validation of Bioanalytical Method - Rote, Ambadas R.; Sonavane, Poonam R. (Current Advances in Chemistry and Biochemistry Vol. 7, 2021)
The determination of telmisartan and hydrochlorothiazide in human plasma using paracetamol as an internal standard has been established using a simple, sensitive, rapid, and economically high performance thin layer chromatographic method.In the treatment of hypertension, a combination of hydrochlorothiazide (HCT) and telmisartan (TEL) is more effective than either drug alone. A mixture of methanol-acetonitrile (3.0:0.1, v/v) was used to collect the plasma sample. For the hydrochlorothiazide and telmisartan calibration curves, concentrations of 200, 400, 600, 800, 1000, and 1200 ng/spots were used, respectively.Telmisartan and hydrochlorothiazide had 75.98% and 81.91%. recovery, respectively. The mobile phase consists of chloroform: methanol: toluene (8:2:4 v/v/v). Densitometric analysis was carried out at wavelength 278 nm. Hydrochlorothiazide, paracetamol, and telmisartan had Rf values of 0.28 0.05, 0.50 0.05, and 0.66 0.05, respectively.During three freeze-thaw cycles (20 C), on bench for 24 hours, and post preparative for 48 hours, the stability of telmisartan and hydrochlorothiazide in plasma was confirmed. The suggested method for determining telmisartan and hydrochlorothiazide in human plasma was statistically validated as well as through a recovery study. The approach is economical and quicker than previously published methods. We can apply this technology for bioequivalence studies in the future.